ANALISIS RASIO KETEBALAN GERAM PADA PROSES PEMBUBUTAN - Samuel Alexander Lepar; Rudy Poeng; I Nyoman Gede (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2015)
ABSTRACT The purpose of this research is to analyze the ratio of the snarled thickness on a lathe machine. The problem of this research is how the influence of the snarled thickness ratio on turning process with varying cutting speed and different cutting depth. Some tests on the turning process on a number of work pieces with same material type and different cutting condition is cerried out. The result shown that higher cutting speed make snarled thickness ratio weaken, while the larger cutting depth make snarled thickness ratio increased. With a 95% confidence level variation of cutting speed will influence to snarled thickness ratio on turning process either 0.25 mm of cutting depth or 1.00 mm of cutting depth Keywords: Snarled thickness ratio, cutting speed, cutting depth, turning process